Faktor Yang Berhubungan Dengan Skrining Hipotiroid Kongenital (SHK) Di Puskesmas Pemurus Dalam - Amanda Maryana Suhendar; Rusmilawaty Rusmilawaty; Rafidah Rafidah; Erni Yuliastuti (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2025)
Background: Congenital Hypothyroid Screening (SHK) in newborns as a preventive treatment integrated with the health system is very important. Detection of thyroid hormone deficiency early in life through SHK allows for early treatment to prevent brain damage. The result coverage of Banjarmasin City Puskesmas was 4,912 (45%) of the target of 11,028 and Pemurus Health Center with a result coverage of 70 infants (26%) who were screened for Congenital Hypothyroidism (SHK) of the target of 260 infants. Objective: To determine the factors associated with Congenital Hypothyroid Screening (SHK) at Pemurus Dalam Health Center. Methods: This study used an analytic descriptive survey with a cross sectional approach. The population in this study were 390 postpartum mothers. The technique used was random sampling technique as many as 80 people. The research instrument used was a questionnaire. Bivariate analysis was performed with the chi square test. Results: That 31 people (61.3%) did not do screening and 49 people (38.8%) did screening. Of the 49 people (61.3%) who did not have anxiety, 6 people (7.5%) had mild anxiety, and 23 people (28.7%) had moderate anxiety and 2 respondents (2.5%) had severe anxiety. 74 people (92.5%) were in geographical locations accessible to health facilities and 6 people (7.5%) were in geographical locations not accessible to health facilities. Statistical test results showed there was a relationship between maternal anxiety p-value = 0.000 and geographical location p-value = 0.001. Conclusion: There is a relationship between anxiety and geographical location at the Pemurus Dalam Health Center in Banjarmasin City. Keywords: Factors, Congenital Hypothyroid Screening, Maternal Anxiety, Geographical Location.